PROGRAM HIDROPONIK SEBAGAI SARANA MENUMBUHKAN JIWA KEWIRAUSAHAAN SISWA SEKOLAH DASAR - Ela Suryani (Universitas Muria Kudus, 2022)
The purpose of this study is to analyze the entrepreneurial spirit of students through a hydroponic program implemented in schools. The research method used is qualitative. The research subjects were the fifth grade students of SDN Susukan 04 Ungaran Timur, Semarang Regency. Data collection techniques through questionnaires, interviews, and documentation. The data validity technique uses source triangulation and technical triangulation. The stages of the hydroponic program to analyze the entrepreneurial spirit are the seeding, seeding, rearing, and harvesting stages. The results showed that the entrepreneurial spirit possessed by students was self-confidence, task and result-oriented, risk-taking, leadership, originality, and future-oriented. The entrepreneurial spirit of the most dominant students appears at the harvest stage when hydroponic plants are ready to be harvested. Meanwhile, the most dominant character of the entrepreneurial spirit possessed by students is self-confidence.